Genital prolapse, prolapse associated restosigmoidea - Case report - Larrea Crovetto, Jorge (2015)
A case presents unusual genital prolapse, associated with a huge rectosigmoid prolapse, perineal treated by a rectosigmoidectomy to Miles, and Manchester operation, in which the broad suturing the levator ani vaginally, they have given us excellent results in a patient who has 6 months of observation.